DOI: 10.1007/978-3-540-71039-4_6
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic and Slide Attacks on KeeLoq

Abstract: Abstract. KeeLoq is a block cipher used in wireless devices that unlock the doors and alarms in cars manufactured by Chrysler, Daewoo, Fiat, GM, Honda, Jaguar, Toyota, Volvo, Volkswagen, etc [8,9,33,34]. KeeLoq is inexpensive to implement and economical in gate count, yet according to Microchip [33] it should have "a level of security comparable to DES".In this paper we present several distinct attacks on KeeLoq, each of them is interesting for different reasons. First we show that when about 2 32 known plai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 16 publications
(28 reference statements)
2
65
0
Order By: Relevance
“…Courtois et al [13] demonstrated a weakness in KeeLog by presenting an attack which requires about 2 32 known plaintexts. For 30% of all keys, the full key can be recovered against a complexity of 2 28 KeeLoq encryptions.…”
Section: Modern Algebraic Tools and Their Applications To Cryptographymentioning
confidence: 99%
“…Courtois et al [13] demonstrated a weakness in KeeLog by presenting an attack which requires about 2 32 known plaintexts. For 30% of all keys, the full key can be recovered against a complexity of 2 28 KeeLoq encryptions.…”
Section: Modern Algebraic Tools and Their Applications To Cryptographymentioning
confidence: 99%
“…Recently SAT solvers have made a great progress in algebraic cryptanalysis. In [5], Bard et al used a SAT solver combined with the slide attack to break Keeloq block cipher. Using SAT solvers, Eibach et al [6] attacked Bivium, a scaled version of Trivium.…”
Section: Attack Descriptionmentioning
confidence: 99%
“…So any CL should have 2 × 56 + 2 × 128 = 368 input contacts for the DES and 2 × 112 + 2 × 128 = 480 input contacts for the Triple DES. Tables 3 and 4 show main characteristics of Circuit Lattices for DES and Triple DES: the number of necessary switches, wires and input contacts, which are computed by formulas (5) and (6) and in Sect. 4.…”
Section: Des and Triple Des Equationsmentioning
confidence: 99%
“…In spite of relatively high worst case bound on l-SAT problem complexity, there exist a number of efficient l-SAT solvers. They became useful tools in cryptanalysis [4,5]. However, an efficient hardware version of the approach is still unknown.…”
Section: Introductionmentioning
confidence: 99%